2021
DOI: 10.3390/ijms22094320
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Control of CAR T Cells

Abstract: Chimeric antigen receptor (CAR) therapy is a promising modality for the treatment of advanced cancers that are otherwise incurable. During the last decade, different centers worldwide have tested the anti-CD19 CAR T cells and shown clinical benefits in the treatment of B cell tumors. However, despite these encouraging results, CAR treatment has also been found to lead to serious side effects and capricious response profiles in patients. In addition, the CD19 CAR success has been difficult to reproduce for othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 155 publications
(195 reference statements)
0
13
0
Order By: Relevance
“…It is important to note that, to date, all CAR studies have, in any case, identified extreme grade 3 or 4 clinical AEs and passed. In the present survey, novel, imaginative ways to deal with managing the flexibility of CAR-T cells by consolidating rather than with exogenous pharmacologic medication (see Table 3 for an outline) [65]. The in vivo process eliminates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is important to note that, to date, all CAR studies have, in any case, identified extreme grade 3 or 4 clinical AEs and passed. In the present survey, novel, imaginative ways to deal with managing the flexibility of CAR-T cells by consolidating rather than with exogenous pharmacologic medication (see Table 3 for an outline) [65]. The in vivo process eliminates.…”
Section: Resultsmentioning
confidence: 99%
“…This treatment also means more and often unexpected aspects, and patients will need careful observation and counseling during the effects and initial verification. Although it is elegant and able to protect patients from unwanted effects, it can be expensive and, when compared to patient-compatible CAR drug costs, may be a small amount of the total treatment cost [65].…”
Section: Gd2mentioning
confidence: 99%
See 2 more Smart Citations
“…They showed that transient “resting” of CAR-T cells improved functionality and may help mitigate exhaustion both functionally and epigenetically, even in “aged” CAR-T cells with constant tonic signaling lasting up to 45 days [ 154 ]. They demonstrated that dasatinib, an FDA-approved multikinase inhibitor [ 155 ], has a similar effect on CAR-T cells underlining its potential clinical application. However, the authors emphasize that their findings contradict those of mouse models in which a late (>14 days) “rescue” of T cells from their cognate antigen did not result in their reinvigoration [ 5 , 11 ].…”
Section: Dysfunctional States Of Car-t Cellsmentioning
confidence: 99%